UTILIZING CARDS AS MEDIA TO IMPROVE STUDENTS' PRE-READING SKILLS - Rosimasnita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by the fact that many students could not read fluently at the beginning and were not able to understand the teacher’s instructions in learning. Through this research, it was expected that word card media could promote students’ pre-reading skills. This research was a classroom action research conducted at grade 2 SDN 21 Mandau. The subjects of this research were 21 students consisting of 12 male students and 9 female students. The data were obtained through reading tests and observations of learning activities. The results in the first cycle showed that the average score of the students’ reading skills was 68.88, in which 13 students reached the KKM. This meant that 61.90% of the students reached the predetermined KKM. Then, in cycle II, the average score of the students' pre-reading skills became 77.46, in which the total number of students reaching the KKM was 18 students with a percentage of 85.71%. Based on the results of this research, it was concluded that the students’ pre-reading skills increased through the use of word cards.